Evaluation of Accuracy of Body Weight Estimation of Female Garut Sheep Using Winter, Schoorl, and Arjodarmoko Formulas - Arif Nugraha, Dimas; Gharizah Alhuur, Ken Ratu; Indrijani, Heni (Bulletin of Applied Animal Research, 2024)
Body weight and measuring body sizes in livestock are important factors in selecting seeds, slaughtering livestock, and describing the condition of livestock. This study aimed to develop a practical method for estimating body weight in female Garut sheep by employing Winter, Schoorl, and Arjodarmoko estimation formulas, and analyzing the correlation between body weight and morphometric measurements, including body length, chest circumference, and shoulder height. The research was conducted on a sample of 23 female Garut sheep aged 18-24 months, utilizing a qualitative descriptive methodology with purposive sampling. Results demonstrated body weight deviation averages as follows: Winter formula 0.74 kg (2.96%), Schoorl formula 2.54 kg (10.21%), and Arjodarmoko formula 1.23 kg (4.95%). Mean body weight estimations were: Winter formula 24.14 ± 3.81 kg, Schoorl formula 27.42 ± 2.65 kg, and Arjodarmoko formula 26.11 ± 4.12 kg. The smallest deviation was observed in the Winter formula (±0.74 kg, 2.96%), followed by Arjodarmoko (1.23 kg, 4.95%), while the Schoorl formula exhibited the largest deviation (2.54 kg, 10.21%). The study concluded that the Winter formula provides the most accurate estimation of body weight for female Garut sheep.